Implementasi Metode Single Minute Exchange of Dies Untuk Optimasi Setting Time Mesin Flexo B1 Grup C Pada Carton Box Departement PT. A - Kusuma, Aldi Dena; Winarsih, Neneng (Fakultas Teknik Universitas Tulang Bawang, 2024)
PT. A is a company engaged in the production and sale of paper, cardboard boxes, and other similar products in Indonesia. The products it offers include paper, tissue, packaging, and other products. The Carton Box Department, from the results of observations made, the average actual setting time on the Flexo B1 Group C machine is 47 minutes/order, this is one of the weaknesses that causes a 32-minute gap from the target set by the company which is 15 minutes/order. The research objectives are to analyze, improve, and obtain improved setting time results on the Flexo B1 Group C machine and the production process time carried out. The SMED (Single Minute Exchange of Dies) method is one approach that can be pursued in improving setting time. The influence of the SMED (Single Minute Exchange of Dies) method in optimizing the setting time of the Flexo B1 Group C machine results in a decrease in setting time with a setup duration of 49.11 minutes, normal time of 59 minutes, and standard time 66 minutes to a setup duration 25.36 minutes, normal time 27 minutes and standard time 34 minutes and the percentage obtained is 51.8%. Keywords: Lean Manufacturing, Productivity, Single Minute Exchange of Dies